Mathematical Models of Synchronous Generators for Different Spatial Distances of Disturbance Point; Mechanical Engineering, Automation and Control Systems (MEACS) - Isaev Yu. N. Yusup Niyazbekovich; Kolchanova V. A. Veronika Andreevna; Tarasenko S. S.; Tikhomirova O. V. (2015, 2015)
Title screen